FAKTOR-FAKTOR PENYEBAB ANAK LULUSAN SD TIDAK MELANJUTKAN KE SLTP - Indah Novita Dewi; Zulkarnain Zulkarnain; Rahma Kurnia Sri Utami (JPG (Jurnal Penelitian Geografi), 2014)
This research emphasizes in assessing about the causative factors of Elementary Students who do not continue to Junior High School in Marga Batin Village, Wawai Karya Region,  East Lampung District in 2009/2012. Subjects of this research are the parents of graduated elementary school students who do not continue to Junior High School.  The research are using descriptive methode. Despite, this research are population research with the total population are 45 families. 1) The low income of parents are around Rp. 300.000,-500.000,- month or 57,8% , the occupation as farmer are 57,8 %, trader 31,1% causing the graduated Elementary Students could not continue to Junior High School. 2) Parents who have Low education level, 44% of them only graduated from Elementary School, make their children as graduated Elementary School Students could not continue to Junior High School. 3) The number of dependent children in the family are  ≥ 3 children, around 64,4%, causing the graduated elementary school students could not continue to junior high school.Penelitian ini bertujuan untuk mengkaji tentang faktor-faktor penyebab anak lulusan SD tidak melanjutkan ke SLTP di Desa Marga Batin Kecamatan Waway Karya Kabupaten Lampung Timur Tahun 2009-2012. Subjek penelitian adalah orang tua dari anak lulusan SD yang tidak melanjutkan ke SLTP, dengan populasi sebanyak  45 KK. Teknik pengumpulan data yang digunakan yaitu teknik wawancara, dokumentasi dan kuesioner 1) Pendapatan orang tua rendah yaitu  Rp 300.000 – 500.000,–/bulan (57,8 %), menyebabkan anak lulusan SD tidak melanjutkan ke SLTP; 2) Tingkat pendidikan orang tua rendah yaitu tamat SD (44 %), menyebabkan anak lulusan SD tidak melanjutkan ke SLTP; 3) Jumlah tanggungan anak dalam keluarga sebanyak ≥ 3 anak sebesar 64,4 %, menyebabkan anak lulusan SD tidak melanjutkan ke SLTP.Kata kunci: anak, lulusan, sekolah